JUAL BELI TANAH ADAT PADA MASYARAKAT HUKUM ADAT DESA WANGEL KABUPATEN KEPULAUAN ARU - Johan Pieter Elia Rumangun (Bajang Institute, 2023)
This Article discusses the sale and purchase of customary land in the Indigenous Law Community of Wangel Village (Aru Islands Regency). The act of free sale of Indigenous Lands has an impact on socio-economic life. A progressive step is needed to anticipate this. So that the issues raised are How to Implement the Sale and Purchase of Customary Land in the People of Wangel Village Customary Law based on Customary Law and what the legal consequences that occur if there is a violation in the Sale and Purchase of Customary Land in the Indigenous Law Community of Wangel Village based on Customary Law. In accordance with the previously mentioned problems, this study is a normative juridical study where the sale and purchase of indigenous land in the Indigenous Law Community of Wangel Village (Aru Islands Regency) is researched through concept approaches, legislative approaches and case approaches. The results of the study showed that the Process of Selling Customary Land has often occurred in the Wangel Village Indigenous Law Community, if there has been a price agreement between buyers and landowners then the buying and selling process will be carried out based on customary law applicable to the Wangel Village Indigenous Law Society. And if there is a violation in the sale and purchase of customary land then the legal consequences are in the form of customary sanctions in accordance with customary law applicable to the Wangel Village Indigenous Law Society